European AIDS Clinical Society Standard of Care meeting on HIV and related coinfections: The Rome Statements. Issue 6 (22nd October 2015) - Mussini, C; Antinori, A; Bhagani, S; Branco, T; Brostrom, M; Dedes, N; Bereczky, T; Girardi, E; Gökengin, D; Horban, A; Lacombe, K; Lundgren, JD; et al.
Abstract : Objectives: The objective of the 1st European AIDS Clinical Society meeting on Standard of Care in Europe was to raise awareness of the European scenario and come to an agreement on actions that could be taken in the future. Methods: Data‐driven presentations were given on specific topics followed by interactive panel discussions. Results: In Eastern European countries, the epidemic is largely driven by injecting drug use, in contrast with Western Europe where the infection mainly occurs through heterosexual contact. A high proportion of people living with HIV remain unaware of their infection. Substantial differences exist in Eastern Europe and Central Asia with respect to treatment coverage, regimen availability and continuity of drug supply. In 2012, tuberculosis case notification rates were 5–10 times higher in Eastern Europe compared with Western Europe, with an alarming proportion of newly diagnosed multi‐drug‐resistant cases. Hepatitis C is widespread in selected geographical areas and risk groups. Conclusions: The key conclusion from the meeting was that a high‐priority group of actions could be identified, including: increasing HIV awareness and testing, improving training for health care providers, ensuring equitable patient access to treatments and diagnostics for HIV and comorbidities, and implementing best practices in infection control and treatment of HIV‐infected patients coinfected with tuberculosis and hepatitis C virus, for whom direct acting antiviral treatment. should be considered.